Emerging technologies and technological catch-up in the pharmaceuticals sector in South Africa - Singh, Vyasha (University of the Witwatersrand, Johannesburg, 2023)
This study investigates the establishment and evolution of innovation capabilities in synthetic biology, an emerging technology used as a mechanism for technological catch-up in latecomer countries, for application in the South African pharmaceuticals sector which aims to make innovative health treatments more accessible to patients, especially those in developing countries. There is a crucial need for developing countries to obtain endogenous technological and innovation capabilities as these are vital for achieving progress with regards to a countries desire to catch-up to leading nations. The qualitative research design used a longitudinal case study approach to determine how the development of capabilities in synthetic biology has evolved in South Africa since its inception at a dedicated research centre established in 2007 by The South African Council for Scientific and Industrial Research (CSIR). Two innovation capability frameworks were applied to assess these capabilities to determine the current level of innovation capability in relation to its technology development, operations, management, and transactions capabilities which ultimately inform its innovation performance. The study utilized data from interviews with individuals directly involved with the centre’s research and management activities; a categorical questionnaire seeking data on technology development activities; as well as data extracted from organizational operational reports and strategic plans. The key findings showed that South Africa has a shortage of skilled human capital in synthetic biology coupled with insufficient financial resources to enable the area to realise its full potential. Therefore the innovation capability ranking of the centre has stagnated at an incremental/ intermediate level. The resulting effect is that, despite the national goals it has set out to achieve, the area has yet to create real impact for the pharmaceutical sector. The recommendations provided at the end of the study will advise the centre on possible pathways it could take to improve its overall innovation capability. At this present level, technological catch-up by means of leapfrogging, remains out of reach, and will hinder the countries progress in closing the gap between itself and leading countries in terms of the rates of technical change with respect to synthetic biology
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Innovation Studies to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Innovation capability; Emerging technologies; Technological catch-up; Sectoral Systems of Innovation; National Systems of Innovation; Synthetic Biology; Pharmaceuticals; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-3: Good health and well-being